Comparison of visfatin levels before and after non-surgical periodontal therapy: A systematic review and meta-analysis - Zahra Tajik; Hamid Mehrafarid; Mojtaba Bayani; Amir Almasi-Hashiani (PLoS ONE, 2025)
Periodontitis is an inflammatory disease and involves a severe inflammation of the periodontium. On the other hand, visfatin is known as one of the inflammatory markers and can probably preserve inflammation in immune cells. Therefore, the purpose of this systematic review and meta-analysis is to compare the mean visfatin level before and after non-surgical periodontal treatment (NSPT). In this systematic review and meta-analysis, to find relevant studies, PubMed, Web of Science and Scopus were searched. Google Scholar was used to review gray literature. Standardized mean difference (SMD) along with 95% confidence interval (95%CI) was calculated. To perform the meta-analysis, in cases where there was significant heterogeneity between the studies, the random-effects model was used, otherwise the fixed-effects model was used. Sixteen studies were included in the meta-analysis. The results show that one month after the NSPT, there was no significant difference in the mean visfatin level of GCF (SMD: -3.91, 95%CI: -9.83, 2.01, p = 0.195, I-square, 96.6%, random effect model, n = 2) and serum (SMD: -0.33, 95%CI: -0.98, 0.33, p = 0.332, fixed effect model, n = 1), but 2, 3 and 6 months after NSPT, the mean visfatin level of GCF and serum decreased significantly. There is no significant difference one month after NSPT in diabetic patients (SMD: -5.83, 95%CI: -15.5, 3.83, p = 0.237, I-square, 97.4%, random effects model, n = 2), but three (SMD: -2.44, 95%CI: -3.37, -1.15, p = 0.001, I-square, 75.9%, random effects model, n = 3) and six months (SMD: -2.41, 95%CI: -3.81, -1.01, p = 0.001, I-square, 78.7%, random effects model, n = 2) after the treatment, a significant decrease is observed in the mean GCF visfatin level. Following the NSPT, the mean visfatin level of GCF, serum and saliva decreases, and in longer follow up time, the level of visfatin decreases significantly. Also, the mean GCF level of diabetic patients decreased after NSPT. Therefore, visfatin level may be used as a diagnostic and therapeutic noninvasive biomarker in patients with periodontitis, which requires further studies.